The Role of Artificial Intelligence in Improving 21st-Century Competencies of Agricultural Students: Literature Review - Haerawati; Suhardi; Risqah Amaliah Kasman (Cerdas: Jurnal Ilmu Pendidikan Sosial dan Humaniora, 2025)
The rapid development of Artificial Intelligence (AI) has driven significant transformations in higher education, including in the field of agriculture, which faces complex challenges such as climate change, food security, and the growing demand for data-driven agricultural systems. Agricultural students are required not only to master technical knowledge but also to develop 21st-century competencies, including critical thinking, creativity, collaboration, communication, and digital literacy. However, comprehensive studies that systematically examine the role of AI in enhancing these competencies within the context of agricultural higher education remain limited and fragmented. Therefore, this study aims to systematically review the role of Artificial Intelligence in improving 21st-century competencies among agricultural students through a literature review approach. The study adopts the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines by conducting a structured literature search across Scopus, Web of Science, ERIC, ScienceDirect, and Google Scholar. Following the selection process, 35 relevant articles were included and analyzed using thematic analysis. The findings indicate that AI technologies, such as machine learning, intelligent tutoring systems, virtual laboratories, and decision support systems, significantly contribute to the enhancement of critical thinking, problem-solving skills, and digital and data literacy among agricultural students. However, the development of creativity, collaboration, and communication skills largely depends on pedagogical designs that actively integrate AI into project-based and collaborative learning environments. In conclusion, AI should be positioned as a pedagogical enabler that supports human-centered learning to prepare agricultural graduates who are adaptive, competent, and ready to address contemporary agricultural challenges.